2018
DOI: 10.3390/ma11122501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Alternating Magnetic Field/Ag Multi-Alloying Combined Solidification Process on Cu–14Fe Alloy

Abstract: An alternating magnetic field (AMF)/Ag multi-alloying combined process was applied to the solidification of Cu–14Fe alloy to study its effects on the microstructure and properties of the resulting samples. The applied AMF and Ag multi-alloying had positive effects on the refinement of the primary Fe phase and precipitation of Fe solute atoms, respectively. These results indicated that the combined AMF/Ag multi-alloying process was effective to improve the distribution of the primary Fe phase and reduce the Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…However, these alloys normally exhibit a lower electrical conductivity and microhardness compared with that of other Cu-based alloys, which is attributed to the relatively higher solubility of Fe in Cu at high temperatures and slow kinetics of Fe precipitation at lower temperatures [3]. In order to improve the strength and conductivity of the Cu–Fe system alloys, many methods including thermo-mechanical treatments and adding other alloying elements have been widely investigated [4,5,6,7,8,9,10,11]. It is found that each element added into the Cu–Fe system alloys can influence the mechanical and electrical properties in various distinct ways.…”
Section: Introductionmentioning
confidence: 99%
“…However, these alloys normally exhibit a lower electrical conductivity and microhardness compared with that of other Cu-based alloys, which is attributed to the relatively higher solubility of Fe in Cu at high temperatures and slow kinetics of Fe precipitation at lower temperatures [3]. In order to improve the strength and conductivity of the Cu–Fe system alloys, many methods including thermo-mechanical treatments and adding other alloying elements have been widely investigated [4,5,6,7,8,9,10,11]. It is found that each element added into the Cu–Fe system alloys can influence the mechanical and electrical properties in various distinct ways.…”
Section: Introductionmentioning
confidence: 99%